Penerapan Teknik Steganografi LSB pada Format Gambar Modern - Ananda Krisna, I Gusti Ngurah Febri; Eka Karyawati, Anak Agung Istri Ngurah (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2024)
As the digital era advances, protecting sensitive information becomes crucial. One approach used is the steganography technique, which involves hiding secret messages in plain-looking media. In this context, the LSB (Least Significant Bit) steganography technique emerged as a common choice, exploiting changes in the least significant bits of media such as images to hide secret messages. This research aims to analyze and apply LSB steganography techniques in modern image formats such as PNG, WEBp, JPEG, BMP, TIFF, HEIF, GIF, and SVG. Through implementation in the form of a computer program with the python programming language, this research evaluates the performance of the technique and makes it applicable in various real-world scenarios. It is hoped that this research can contribute to the development of more effective information security solutions and become the basis for further research in the field of steganography and information security as a whole. The results obtained from this research are that the encryption process of modern image formats has a success rate of 81.25% with an average successful sample encryption speed of 1.55 seconds. and the modern image format decryption process has a success rate of 81.25% with a text match rate of 69.23%.